Perbandingan Kinerja Ipcop dengan Honeypot dalam Mengamankan Server Linux dari Serangan Hacker: Array - Manik, Burju Manik; Lubis, Imran (Universitas Harapan Medan, 2021)
Research to install IPCop and honeypot on server computers and implement IPCop by way of configuration to protect the server from unauthorized parties. The software used in this research is IPCop, Manjaro Linux, Shootpress, Windows 10, and Virtual Box. The results of this study indicate that the implementation of IPCop as a security system on the server can be done and can run well. IPCop is able to protect servers from hacker attacks very well, even using IPCop hackers are not able to ping the server, so hackers cannot find out information about the target server. Honeypot implementation as a security system on a linux server can be done and can run well. Honeypot is able to protect the server from hacker attacks well through its virtual server. So that hackers do not know where the original server is and the hacker will only attack the virtual server from the honeypot and think as if the server is the real server. In this case IPCop is better than the honeypot in the server security system